Assessment of Luminescent Downshifting Layers for the Improvement of Light‐Harvesting Efficiency in Dye‐Sensitized Solar Cells. Issue 17 (18th September 2014) - Hosseini, Zahra; Diau, Eric Wei‐Guang; Mehrany, Khashayar; Taghavinia, Nima
Abstract Luminescence downshifting (LDS) of light can be a practical photon management technique to compensate the narrow absorption band of high‐extinction‐coefficient dyes in dye‐sensitized solar cells (DSSCs). Herein, an optical analysis on the loss mechanisms in a reflective LDS (R‐LDS)/DSSC configuration is reported. For squaraine dye (550–700 nm absorption band) and CaAlSiN3:Eu2+ LDS material (550–700 nm emission band), the major loss channels are found to be non‐unity luminescence quantum efficiency (QE) and electrolyte absorption. By using an ideal LDS layer (QE=100 %), a less absorbing electrolyte (Co‐based), and antireflection coatings, approximately 20 % better light harvesting is obtained. If the absorption/emission band of dye/LDS is shifted to 800 nm, a maximal short‐circuit current density (Jsc) of 22.1 mA cm−2 can be achieved. By putting the LDS layer in front of the DSSC (transmissive mode), more significant loss channels are observed, and hence a lower overall efficiency than the R‐LDS configuration.